2022
DOI: 10.1055/a-2004-6485
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Organic Electrochemistry Catalyzed by Transition Metals

Abstract: Asymmetric catalysis is one of the most important areas of organic synthetic chemistry. In recent years, with the revival of organic electrochemistry, scientists have begun to try to combine asymmetric catalysis with electrochemistry to build valuable chiral molecules. In this review, we focus on examples of organic electrochemistry catalyzed by transition metals. According to the classification of the catalyst’s interaction with the substrate, we can divide them into two categories: 1) transition-metal cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…36-1451), which are the characteristic peaks of ZnO impurity were produced between zinc nitrate and triethylamine. 32 Morphology of MOF-5-NH 2 /Urushiol/PVP Nanofiber Composite Film. Figure 3 show the SEM images of the crystals with different contents of MOF-5-NH 2 added separately with a urushiol/PVP ratio of 1:1 substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36-1451), which are the characteristic peaks of ZnO impurity were produced between zinc nitrate and triethylamine. 32 Morphology of MOF-5-NH 2 /Urushiol/PVP Nanofiber Composite Film. Figure 3 show the SEM images of the crystals with different contents of MOF-5-NH 2 added separately with a urushiol/PVP ratio of 1:1 substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The SEM image of Figure a shows that the whole sample exhibits the phenomenon of agglomeration of many tiny crystals with irregular surface, and its morphological appearance is similar to that of MOF-5 crystals prepared by taking the direct mixing method. It is speculated that the reason may be related to the easy formation of hydrogen bonds between amino groups and amino acids with each other. , The presence of amino functional group was initially proved by the asymmetric and symmetric stretching vibrations of –NH 2 that can be found at 3120 and 3320 cm –1 in the infrared spectra of the MOF-5-NH 2 crystals in Figure b, in which 1560 and 1390 cm –1 corresponded to the asymmetric and symmetric vibrations of the carbonyl group in the carboxylate group, respectively, and the absorption peaks at 1030 cm –1 were attributed to the bending vibration in the C–H plane, and the absorption peaks at 850 and 772 cm –1 corresponded to the bending vibration out of the C–H plane. Moreover, compared with the XRD pattern of the MOF crystals synthesized in the reference, three characteristic peaks located at 6.8, 9.6, and 13.7° were seen in the XRD pattern of the MOF-5-NH 2 crystals prepared in this experiment, which proves the similarity of the crystalline structure between the two (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although higher ee values are required for applications, asymmetric electrochemistry towards chiral scaffolds is a highly interesting concept gaining increased attention. [125][126][127][128][129] (Di)carboxylation of simpler alkenes seems more challenging as literature reports are scarce. 130 Nam and coworkers (entry 8) reported that even small amounts of water guide the selectivity of styrene carboxylation towards dicarboxylation or b-hydrocarboxylation.…”
Section: Carboxylations Involving Double Bondsmentioning
confidence: 99%
“…3 Lu and his team delve into transition-metal electrochemical asymmetric catalysis including the recently emerged photoelectrochemical asymmetric catalysis (PEAC). 4 Phillips, Pombeiro, and associates encapsulate the power of electrochemistry in catalytic enantioselective synthesis. 5 Zhang, Liu, and their team offer a comprehensive summary of electrochemical cascade cyclization reactions used in carbon ring and heterocycle production.…”
mentioning
confidence: 99%